Prospective Intraindividual Comparison of Magnetic Resonance Imaging With Gadoxetic Acid and Extracellular Contrast for Diagnosis of Hepatocellular Carcinomas Using the Liver Imaging Reporting and Data System - Min, Ji Hye; Kim, Jong Man; Kim, Young Kon; Kang, Tae Wook; Lee, Soon Jin; Choi, Gyu Seong; Choi, Seo Youn; Ahn, Soohyun (Hepatology, 2018)
We intraindividually compared the efficacy of magnetic resonance imaging (MRI) with extracellular contrast agents (ECA-MRI) and MRI with hepatobiliary agents (HBA-MRI) for the diagnosis of hepatocellular carcinoma (HCC) using the Liver Imaging Reporting and Data System (LI-RADS). Between November 2016 and November 2017, we enrolled 91 patients with chronic liver disease who underwent both ECA-MRI and HBA-MRI within a 1-month interval for a first detected hepatic nodule on ultrasound. In total, 117 observations (95 HCCs, 19 benign lesions, and 3 other malignancies; median size, 18 mm) were identified with surgical resection. Two observers assessed two MRIs based on LI-RADS v2017, with consensus by a third observer. We then compared the diagnostic performance of LR-5 according to LI-RADS and modified LI-RADS. ECA-MRI had higher sensitivity (77.9% versus 66.3%) and accuracy (82.1% versus 72.6%) than HBA-MRI in the LR-5 category (P < 0.001). When applying either modified washout on the portal venous phase (PVP)/transitional phase (TP) of HBA-MRI or isointensity with a capsule during the PVP/delayed phase of ECA-MRI (illusional washout), 13 HCCs on HBA-MRI and 11 HCCs on ECA-MRI were correctly classified as HCC, while achieving 100% specificity. One cholangiocarcinoma was accurately classified only with HBA-MRI due to its targetoid appearance in the TP and hepatobiliary phase. Conclusion: ECA-MRI showed better sensitivity and accuracy than HBA-MRI for the diagnosis of HCC with LI-RADS. We achieved better diagnostic performance when applying a modified washout on PVP/TP HBA-MRI and an illusional washout on ECA-MRI than we did with conventional criteria.
Keywords: Adult; Aged; Carcinoma, Hepatocellular; Contrast Media; Female; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies